A Snapshot of Transdermal and Topical Drug Delivery Research in Canada - Mahdi Roohnikan; Elise Laszlo; Samuel Babity; Davide Brambilla (MDPI AG, 2019)
The minimally- or non-invasive delivery of therapeutic agents through the skin has several advantages compared to other delivery routes and plays an important role in medical care routines. The development and refinement of new technologies is leading to a drastic expansion of the arsenal of drugs that can benefit from this delivery strategy and is further intensifying its impact in medicine. Within Canada, as well, a few research groups have worked on the development of state-of-the-art transdermal delivery technologies. Within this short review, we aim to provide a critical overview of the development of these technologies in the Canadian environment.